(untitled) (Sustainability in Debate, 2021)
This article explores the potential of dialogue networks as tools for valuing rural women and overcoming the traditional marginalization of rural women in the countryside. The guiding hypothesis is that when given opportunities to co-produce solutions in a participatory manner and an enabling environment, women can articulate and express their challenges and visualize desirable futures. The results confirm this hypothesis to the extent that women experience and execute these premises in the established spaces of dialogue. The recommendations are for the promotion of actions and policies that provide environments in which women can reframe their role in society and the family.